Evaluation of the immunomodulatory ability of lactic acid bacteria isolated from feedlot cattle against mastitis using a bovine mammary epithelial cells In vitro assay - Fukuyama, Kohtaro (2020)
Bovine mastitis, the inflammation of the mammary gland, affects the quality and quantity of milk yield. Mastitis control relies on single or multiple combinations of antibiotic therapy. Due to increasing antibiotic resistance in pathogens, the intramammary infusion of lactic acid bacteria (LAB) has been considered as a potential alternative to antibiotics for treating and preventing bovine mastitis through the improvement of the host immunity. Probiotic effects are a strain-dependent characteristic; therefore, candidate LAB strains have to be evaluated efficiently to find out the ones with the best potential. Here, we investigated LAB strains originally isolated from feedlot cattle’s environment regarding their ability in inducing the Toll-like receptor (TLR)-triggered inflammatory responses in bovine mammary epithelial (BME) cells in vitro. The BME cells were pre-stimulated with the LAB strains individually for 12, 24, and 48 h and then challenged with Escherichia coli-derived lipopolysaccharide (LPS) for 12 h. The mRNA expression of selected immune genes—interleukin 1 alpha (IL-1α), IL-1β, monocyte chemotactic protein 1 (MCP-1), IL-8, chemokine (C-X-C motif) ligand 2 (CXCL2), and CXCL3 were quantified by real-time quantitative PCR (RT-qPCR). Results indicated that pretreatment with some Lactobacillus strains were able to differentially regulate the LPS inflammatory response in BME cells; however, strain-dependent differences were found. The most remarkable effects were found for Lactobacillus acidophilus CRL2074, which reduced the expression of IL-1α, IL-1β, MCP-1, IL-8, and CXCL3, whereas Lactobacillus rhamnosus CRL2084 diminished IL-1β, MCP-1, and IL-8 expression. The pre-stimulation of BME cells with the CRL2074 strain resulted in the upregulated expression of three negative regulators of the TLRs, including the ubiquitin-editing enzyme A20 (also called tumor necrosis factor alpha-induced protein 3, TNFAIP3), single immunoglobin IL-1 single receptor (SIGIRR), and Toll interacting protein (Tollip) after the LPS challenge. The CRL2084 pre-stimulation upregulated only Tollip expression. Our results demonstrated that the L. acidophilus CRL2074 strain possess remarkable immunomodulatory abilities against LPS-induced inflammation in BME cells. This Lactobacillus strain could be used as candidate for in vivo testing due to its beneficial effects in bovine mastitis through intramammary infusion. Our findings also suggest that the BME cells immunoassay system could be of value for the in vitro evaluation of the immunomodulatory abilities of LAB against the inflammation resulting from the intramammary infection with mastitis-related pathogens.